MHD Stagnation Point Radiative Flow of Hybrid Casson Nanofluid Across a Stretching Surface (Contemporary Mathematics, 2024)
The current investigation explores the hybrid Casson nanofluid stagnation point flow on a transient stretching surface under the impact of thermal radiation. The Joule heating effect is also considered in this study. Copper and aluminium hybrid nanoparticles are used. The guiding partial differential equations are broken down into nonlinear ordinary differential equations using adequate affinity transmutations. The subsequent equations are worked out by employing the Keller box scheme. The numerical findings for the study are represented by plotting velocity, and temperature graphs for various parameters like radiation parameter (Rd), Casson parameter (β), magnetic parameter (M), Prandtl number (Pr), and unsteady parameter (s). As well, the local parameters coefficient of skin friction is calculated. For progressive estimates of the Casson parameter, the velocity of the liquid flow reduces. On intensifying the Prandtl number temperature of the fluid diminishes. Also, the effect of nanoparticles volume fraction of both nanoparticles is observed. It was found that for escalating values of both nanoparticle velocities, the velocity of the fluid flow reduces and the opposite trend is observed for the temperature profile. The usage of hybrid nanofluids has the advantage of heat transfer enhancement. The outcomes of the current investigation are good and in congruence with existing literature.
Keywords: casson fluid; hybrid nanofluid; MHD; radiation; keller box method